Funkcional'nyj trening lic s amputaciej nižnich konecnostej - Semenova, S. A.; Khrekin, D. O. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The article analyzes the means and methods of physical culture used in the rehabilitation of persons with lower limb amputation. The authors identified the main problems faced by amputees when placing them on prostheses. The article tests the author`s method of functional training of this group of people, analyzes its effectiveness.